2014
DOI: 10.1007/s10903-014-0117-5
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Beliefs and Understandings of Cervical Cancer Among Mexican Immigrant Women in Southeast Georgia

Abstract: Rural Mexican immigrant women in the U.S. are infrequently screened and experience health disparities from cervical cancer. We explored cancer-related cultural beliefs in this population. We administered a cross-sectional survey to 39 Mexican immigrant women due for screening. We conducted univariate and bivariate analyses of participants’ characteristics, Pap test history, cancer-related knowledge and beliefs, and cultural consensus analysis about causes of cervical cancer and barriers to screening. For all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 32 publications
3
10
0
2
Order By: Relevance
“…As Kenya and other LMICs of SSA continue with HPV vaccination program, this alone will not be effective in the absence of community sensitization and continued screening. Most importantly, however, is the recognition that even with advanced education, as demonstrated in this study, the decision to screen for cervical cancer may significantly be influenced by other factors including cultural and religious values that have a significant bearing on the decisions that people make on a daily basis (30)(31)(32).…”
Section: Discussionmentioning
confidence: 84%
“…As Kenya and other LMICs of SSA continue with HPV vaccination program, this alone will not be effective in the absence of community sensitization and continued screening. Most importantly, however, is the recognition that even with advanced education, as demonstrated in this study, the decision to screen for cervical cancer may significantly be influenced by other factors including cultural and religious values that have a significant bearing on the decisions that people make on a daily basis (30)(31)(32).…”
Section: Discussionmentioning
confidence: 84%
“…In this study, 441 women were contacted to identify 90 women who would soon not be up-to-date with their cervical cancer screening. The 2 years gap in screening was used instead of 3 years as the inclusion criteria because of the difficulty in locating women who would qualify for the study, which was identified as a problem in our pilot survey study [20]. However, during the charlas , the promotora told participants they should receive a Pap test every 3 years.…”
Section: Discussionmentioning
confidence: 99%
“…Respecto a las barreras relacionadas con las características del examen, los resultados reportados concuerdan con investigaciones previas donde se señala la vergüenza que genera el examen 14,16,[20][21][22] y el miedo que les provoca el diagnostico de cáncer 4,6,16,23 . En relación a esto último, se ha descrito que hay mujeres que prefieren "no saber de enfermedades que no tienen tratamiento y que pueden llevar a la muerte" 19,22 .…”
Section: Discussionunclassified